2001
DOI: 10.1002/jrs.687
|View full text |Cite
|
Sign up to set email alerts
|

The Raman spectra of Cr3O8 and Cr2O5

Abstract: The Raman spectra of polycrystalline Cr 3 O 8 and Cr 2 O 5 powders were measured. The powders were prepared by thermal decomposition of CrO 3 under flowing oxygen. Their composition was verified with x-ray diffraction. Raman spectra were excited with both 514.5 and 647.1 nm radiation. The spectral intensities were corrected for wavelength-dependent instrumental response. Tentative peak descriptions were made by comparison of the Cr 3 O 8 and Cr 2 O 5 spectra with reported spectra of crystalline chromium oxides. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…3 in the spectra acquired at t ϭ 9.6 h and t ϭ 14.5 h. The small band is not currently identified, but several Cr VI species scatter in that general region and it is possible that the small 800 cm Ϫ1 band arose from some type of Cr VI species. 9,22 Two other bands in Fig. 3 merit discussion.…”
Section: Resultsmentioning
confidence: 98%
“…3 in the spectra acquired at t ϭ 9.6 h and t ϭ 14.5 h. The small band is not currently identified, but several Cr VI species scatter in that general region and it is possible that the small 800 cm Ϫ1 band arose from some type of Cr VI species. 9,22 Two other bands in Fig. 3 merit discussion.…”
Section: Resultsmentioning
confidence: 98%
“…2). It has been suggested that these vibrations may be associated with the spectral features of edge-sharing Cr III O 6 octahedra and possibly the O-Cu I -O linear bond [24]. As shown in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 96%
“…For x = 0, it shows three typical vibration modes at 209, 455, and 705 cm −1 , which are identified as σ(A g ), σ(E g ) and σ(A 1g ) modes, respectively. These modes have been supposed to be associated with the spectral features of the edge‐sharing CrO 6 octahedra and possibility the O–Cu–O linear bond . The A 1g and E g modes correspond to the vibrations of Cu–O bonds along the c ‐axis and vibrations in the triangular lattice perpendicular to the c ‐axis, respectively .…”
Section: Resultsmentioning
confidence: 99%